2008
DOI: 10.1142/s1793292008000940
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance Study of Poly (Ortho-Anisidine)/Single-Walled Carbon Nanotube Composite Films: Spin Dynamics and Effects of Physisorption Processes

Abstract: Poly(ortho-anisidine) (POA)/single-walled carbon nanotubes (SWCNTs) composite films have been prepared by means of oxidative potentiostatic electropolymerization of the monomer (ortho-anisidine) in the presence of purified SWCNTs. The magnetic properties of the obtained films have been investigated by electron spin resonance (ESR) (ν ∼ = 9.4 GHz; temperature range 10-300 K) and compared with those of pure POA films in the same oxidation state. The similarity of the ESR signals and the dependence on temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This phenomenon is indicative of homogeneous reactions between available monomers and oligomers that are followed by polymer nucleation and growth on the electrode surface 39,40. At this scan rate, we also observe peaks at about 1.4 V (P1) and 1.6 V (P2) corresponding to the oxidation of the monomer diffusing in proximity to the electrode surface31,41 and the overoxidation of the polymer film, respectively 42,43. During overoxidation, the radical cations contained in the oxidized polymer chains react with the products of water electrolysis, contributing to film degradation and loss of electroactivity 43…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…This phenomenon is indicative of homogeneous reactions between available monomers and oligomers that are followed by polymer nucleation and growth on the electrode surface 39,40. At this scan rate, we also observe peaks at about 1.4 V (P1) and 1.6 V (P2) corresponding to the oxidation of the monomer diffusing in proximity to the electrode surface31,41 and the overoxidation of the polymer film, respectively 42,43. During overoxidation, the radical cations contained in the oxidized polymer chains react with the products of water electrolysis, contributing to film degradation and loss of electroactivity 43…”
Section: Resultsmentioning
confidence: 65%
“…Although previous studies have shown that electrode surface morphology is especially crucial in improving the efficiency of living photovoltaics,23,24 comparisons have largely been limited to morphologically distinct electrodes synthesized with different materials and preparative procedures. CPs offer one approach to designing electrodes with tunable chemical structure, reactivity, morphology, as well as electrochemical and electrical properties once the synthesis conditions have been optimized 31–34. In previous studies, Tamburri et al focused on a systematic investigation of the polymerization conditions that allow to decouple the effects of various synthesis experimental parameters on the electrocatalytic, electrochemical, and electrical performance of CP electrodes.…”
Section: Introductionmentioning
confidence: 99%
“… The results are presented in Table 3, with A / B the ratio of the height of the positive to the negative peak. All samples had g values in the range 2.0040 ± 0.00008, which is usually ascribed to polaron states, i.e., paramagnetic charge carrier species 48. All the polymers displayed a single signal, indicating that the conduction mechanism was of polaron nature, whereas diamagnetic properties are of bipolaron nature.…”
Section: Resultsmentioning
confidence: 98%
“…However, further studies indicated that measurements of the hydrogen storage capacity of metal‐decorated carbonaceous supports vary from an enhancement of several times to negligible within the experimental uncertainty. These occurrences were alternately imputed to a decrease/modification of the available adsorption surface area after metal doping, to the formation of new chemical bonds between hydrogen and the sorbent supports, and to side‐reactions that involve either the oxidized metal nanoparticles or residual organics left from the metal precursors . Indeed, such investigations were performed with different support materials (which included superactivated carbon, activated carbon fibers, carbon nanotubes, covalent organic frameworks, various nanostructured, and templated carbons) and by using different measurements techniques (which included volumetric gas adsorption analysis, inelastic neutron scattering, and vibrational spectroscopy) .…”
Section: Resultsmentioning
confidence: 99%